THE SKAZ FICTIONAL NARRATIVE AND THE NOVEL FORM In MILEN RUSKOV'S CHAMKORIA - Denitsa ASTAHOVA (Linguarum Universe)
The article examines the issue of the interaction of two artistic strategies in the poetics of the novel Chamkoria (2017) by Milen Ruskov - the skaz fictional narrative and the genre form of the novel. The skaz narrative is presented as a subtype of first-person narration, which manifests its peculiarities in the construction of the narrator character, the plot-compositional features of the work and the speech expression of the narrator. The views and preferences of the writer on the merits of the first-person narration are analyzed. A comparison with the third-person narrative is proposed, whose artistic choice gives specific advantages in recreating the complex subject matter of the tragic national political events of the first half of the 20th century thematized in the novel. Chamkoria is a novel experiment that seeks not only ways for its own construction, but also for modern Bulgarian fiction.